2007
DOI: 10.1002/jhet.5570440231
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dibromo‐5,5‐dimethylhydantoin (DBH) as an efficient promoter for acetylation of 3‐arylsydnones in the presence of acetic anhydride under neutral conditions

Abstract: 1,3‐Dibromo‐5,5‐dimethylhydantoin (DBH) has been found to efficiently promote the conversion of various 3‐arylsydnones to their 4‐acetyl congeners in the presence of acetic anhydride under neutral conditions in satisfactory yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2245 DBH has also found applications as a catalyst in the oxidations of pyrazolines. 2246 Conversion of various 3-arylsydnones to their corresponding 4-acetyl derivatives was achieved using DBH as the catalyst (Scheme 840). 2247 The products were achieved by treating the precursor 3-arylsydnones with acetic anhydride in the presence of a catalytic amount of DBH at reflux temperature.…”
mentioning
confidence: 99%
“…2245 DBH has also found applications as a catalyst in the oxidations of pyrazolines. 2246 Conversion of various 3-arylsydnones to their corresponding 4-acetyl derivatives was achieved using DBH as the catalyst (Scheme 840). 2247 The products were achieved by treating the precursor 3-arylsydnones with acetic anhydride in the presence of a catalytic amount of DBH at reflux temperature.…”
mentioning
confidence: 99%
“…DBH has been found to efficiently catalyze the conversion of various 3-arylsydnones to their corresponding 4-acetyl derivatives in the presence of acetic anhydride under neutral conditions in satisfactory yields (Scheme 94) [110]. …”
Section: Scheme 92mentioning
confidence: 99%
“…Thirdly, other researchers proved that acetic anhydride can convert the dextro-rotary N-nitroso-N-phenylalanine into the optically inactive N-phenyl-C-methylsydnone (IV). The loss of optical activity implies either racemization or a change in the hybridization of C4 from a chiral sp 3 . The oxygen atom attached to C5 was proved to be in an enolate form due to the rapid formation of a monobromo derivative (V) in glacial acetic acid and bromine [10].…”
Section: Definition Of Sydnonementioning
confidence: 99%
“…The most potent agents were found to have a chloride or methyl substituent on the stilbene moiety with a phenyl or methyl group at C4 of the sydnone ring like in structures XXXVIII and XXXIX [61]. Others reported a significant anticancer activity for new sydnones derivatized with imidazo [2,1-b] [1,3,4] thiadiazole and coumarin at C4 of the sydnone ring (XL) against HT-29 human colorectal adenocarcinoma cell line. They found that the hydrophobicity of R was crucial for the cytotoxic activity and the existence of a chlorine atom on the coumarin ring (R 1 ) sharply raised the activity to be comparable to that of cisplatin [62].…”
Section: Cytotoxic and Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation